2015
DOI: 10.1097/prs.0000000000001557
|View full text |Cite
|
Sign up to set email alerts
|

TUGs into VUGs and Friendly BUGs

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…In our review, when two TUG flaps were inserted to make one breast, the thoracodorsal arteries were predominantly the recipient of choice for the second flap (Schoeller et al, 2008;Werdin et al, 2016). This cumbersome process may be the result of the short pedicle length to reach the retrograde internal mammary vessels upon flap stacking, although Park et al reported some exceptions (Park et al, 2015). In contrast, most of the stacked PAP flap cases utilized retrograde internal mammary vessels without any special notes.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In our review, when two TUG flaps were inserted to make one breast, the thoracodorsal arteries were predominantly the recipient of choice for the second flap (Schoeller et al, 2008;Werdin et al, 2016). This cumbersome process may be the result of the short pedicle length to reach the retrograde internal mammary vessels upon flap stacking, although Park et al reported some exceptions (Park et al, 2015). In contrast, most of the stacked PAP flap cases utilized retrograde internal mammary vessels without any special notes.…”
Section: Discussionmentioning
confidence: 88%
“…Studies not relevant (74 articles), cadaver or imaging studies (4 articles), case reports (3 articles), reviews (5 articles), and reports in languages other than English (5 articles) were further excluded, resulting in 21 articles for full-text review. After excluding three articles lacking extractable data or with suspected cohort overlap, we identified 16 articles for systematic analysis(Figure 1a)(Arnez et al, 2004;Bodin et al, 2015;Bodin et al, 2016;Buntic, Horton, Brooks, & Althubaiti, 2011;Craggs et al, 2014;Fansa, Schirmer, Warnecke, Cervelli, & Frerichs, 2008;Fattah, Figus, Mathur, & Ramakrishnan, 2010;Hunter, Lardi, Dower, & Farhadi, 2015;Kind & Foster, 2008;Locke, Zhong, Mureau, ;Park, Alkureishi, & Song, 2015;Saint-Cyr et al, 2012;Schoeller et al, 2008;Wechselberger et al, 2016;Wechselberger & Schoeller, 2004;Werdin, Haug, Amr, & Schoeller, 2016). The initial PAP flap search yielded 252 articles.…”
mentioning
confidence: 99%
“…In order to address some of these issues, the TUG flap skin paddle design has been modified by some authors, by changing its orientation. These variations, the diagonal/ oblique upper gracilis (DUG) [8] and vertical upper gracilis (VUG) flaps [9], avoid placing a scar on the posterior thigh and ease the closure of the donor site, but do not offer a substantial increase in the overall flap volume which can be harvested.…”
Section: Introductionmentioning
confidence: 99%
“…The need for postoperative lipofilling was significantly higher in double TMG patients (65.1% vs. 38.2%, p = 0.0047, RR 1.71) which was expected due to decreased flap size compared to the double DIEP flap, and therefore, more occasionally, volume insufficiencies. In a recently published study by Park et al, fat grafting was needed in 13 of 22 (59%) TMG patients after unilateral breast reconstruction [ 27 ]. Since a majority of patients will undergo postoperative symmetrization procedures or a nipple areola complex reconstruction, the need for postoperative lipofilling represents no limitation to use double TMG flaps for reconstruction.…”
Section: Discussionmentioning
confidence: 99%